Association between government share ownership, investment opportunity set and corporate policy choices : evidence from Singapore. - Chia, Shu Siang. (2008)
The research is conducted using pooled regression analysis on 223 listed firms on the Singapore Exchange (SGX) between 1994 to 1998. We provide additional evidence on contracting theory arguments for the relation between government ownership of shares, growth opportunities measured in terms of the investment opportunity set (IOS) and corporate policy choices. Consistent with prior studies, we find that IOS is negatively associated with leverage and dividend yield. Our results also show that government ownership is negatively associated with leverage and dividend yield.